2021
DOI: 10.1111/jcmm.16871
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine alleviates hepatic ischaemia‐reperfusion injury via the PI3K/AKT/Nrf2‐NLRP3 pathway

Abstract: Hepatic ischaemia‐reperfusion (I/R) injury constitutes a tough difficulty in liver surgery. Dexmedetomidine (Dex) plays a protective role in I/R injury. This study investigated protective mechanism of Dex in hepatic I/R injury. The human hepatocyte line L02 received hypoxia/reoxygenation (H/R) treatment to stimulate cell model of hepatic I/R. The levels of pyroptosis proteins and inflammatory factors were detected. Functional rescue experiments were performed to confirm the effects of miR‐494 and JUND on hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…It has been shown that the PI3K/AKT/GSK3β signaling pathway plays a pivotal role in alleviating early brain injury in stroke, including SAH and cerebral ischemia (Chen S. et al, 2014 ; Ma et al, 2016 ). A previous study has reported that Dex was able to alleviate hepatic ischemia–reperfusion injury via the PI3K/AKT/Nrf2-NLRP3 pathway (Wu et al, 2021 ). In this study, we also observed that Dex activated the PI3K /AKT/GSK3β pathway at 24 h after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the PI3K/AKT/GSK3β signaling pathway plays a pivotal role in alleviating early brain injury in stroke, including SAH and cerebral ischemia (Chen S. et al, 2014 ; Ma et al, 2016 ). A previous study has reported that Dex was able to alleviate hepatic ischemia–reperfusion injury via the PI3K/AKT/Nrf2-NLRP3 pathway (Wu et al, 2021 ). In this study, we also observed that Dex activated the PI3K /AKT/GSK3β pathway at 24 h after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine (DEX) is a highly selective α2-adrenergic agonist with analgesic, anti-stress, and anti-inflammatory effects and is commonly used as a sedative and anesthetic in clinical practice [ 5 ]. The protective effects of DEX in H/R-mediated organ injuries have been extensively studied, such as in brain [ 6 ], liver [ 7 ], renal [ 8 ]. Additionally, DEX exerts its role in cardiomyocyte through different mechanisms [ 9–12 ].…”
Section: Introductionmentioning
confidence: 99%
“…AKT is a serine/threonine kinase and a downstream signal molecule of PI3K, activated by it ( Li et al, 2017 ). Several studies have reported that the PI3K/Akt pathway is essential for regulating Nrf2/Ho-1 pathway activation and is thus involved in protection against oxidative stress and apoptosis in multiple cell types ( Di Tu et al, 2020 ; Feng et al, 2021 ; Wu et al, 2021 ). Under oxidative stress, the PI3K/Akt signaling pathway leads to Nrf2-dependent transcription and overexpression of HO-1 protein ( He et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%